A novel approximation to the relation between reduced molecular potential of C1-3 hydrocarbon gases and their compressibility factor. (1st November 2016) - Yang, Xiaohong; Zhang, Shunxi; Zhu, Weiling
ABSTRACT: Based on symmetric intermolecular interactions approximation, a novel relation between compressibility (Z) factor of hydrocarbon gases and molecular potential has been developed. The relation indicated that the Z factor was an exponential function of the depth of potential well, which was derived to be proportional to the molecular potential. By this relation, the reduced molecular potentials of methane, ethane, and propane were determined at the same temperature. The obtained reduced potentials appeared the standard L-J curve shape, suggesting the rationality and success of this approximation and showing the academic significance of the relation in estimating molecular potential.